Techies and Firm Level Productivity - James Harrigan; Ariell Reshef; Farid Toubal (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the impact of techies—engineers and other technically trained workers—on firm-level productivity. We first report new facts on the role of techies in the firm by leveraging French administrative data and unique surveys. Techies are STEM-skill intensive and are associated with innovation, as well as with technology adoption, management, and diffusion within firms. Using structural econometric methods, we estimate the causal effect of techies on firm-level Hicks-neutral productivity in both manufacturing and non-manufacturing industries. We find that techies raise firm-level productivity, and this effect goes beyond the employment of R&D workers, extending to ICT and other techies. In non-manufacturing firms, the impact of techies on productivity operates mostly through ICT and other techies, not R&D workers. Engineers have a greater effect on productivity than technicians.
Keywords: D20; D24; F10; F16; F60; F66; J20; J23; J24; O52; 330; productivity; R&D; ICT; techies; STEM skills